PENGARUH FINANCIAL LEVERAGE, PROFITABILITAS, NET PROFIT MARGIN, DAN UKURAN PERUSAHAAN TERHADAP PRAKTIK PERATAAN LABA - Dhea Ramadani Mirwan; Muhammad Nuryatno Amin (AKUNTABILITAS, 2020)
The aim of this research is to prove the effect of financial leverage, profitability, net profit margin and firm size to the income smoothing. Population of this research is manufacturing companies listed at the Indonesia Stock Exchange (BEI) for the period of 2016-2018 with sampling determined by purposive sampling. Data analyzed using logistic regression (binary logistic regresion). The results of this research showed that financial leverage and profitability have negative effect to income smoothing, and at the opposite net profit margin has positive effects  to income smoothing. Whereas firm size has no effects to income smoothing